Virtual Environment Imaging Technology Enhances Maintenance of Biomedical Assets - Muhammad Syukri Imran, Abdullah; Siti Aisyah, Sapiee; Dzatul Ithri, Amran (Lembaga Jurutera Malaysia, 2024)
Government hospitals provide a wide range services and house many facilities including biomedical equipment to ensure 24-hour healthcare services. The hospital’s facility managers need to leverage current resources to ensure minimum interruption to all critical functions which heavily rely on various type of biomedical equipment (BE). There are opportunities to integrate the use of emerging technologies such as 3D virtual environment imaging in facility management services of hospitals. The visualisation capability provided by such technology could greatly improve BE maintenance management process such as BE inventory upkeep, BE operation and routine maintenance processes, BE replacement and upgrades and BE safety and health. It also helps in the disaster management process as seen in increased mobility of BE across the Ministry of Health (MOH) facilities during the recent COVID 19 pandemic. The feasibility and acceptability of such technology in BE management should be further explored to optimise disaster response as well as out-of-hospital management of BE. MOH have taken a keen interest in such technology and is moving forward to test and implement such tools in this era of distance learning and distance managing.